Prevalence and clinicopathologic association of LMP1 and P16 expression in nasopharyngeal carcinoma tissue in Hospital Universiti Sains Malaysia - Ibrahim, Noorul Balqis Che (2020)
Introduction : This study is to determine the prevalence of expression of LMP 1 and P16 proteins and the clinicopathology data of the nasopharyngeal carcinoma (NPC) cases in Hospital Universiti Sains Malaysia (HUSM). The association between the expression of LMP1 and P16 proteins in NPC with its clinicopathological parameters was then investigated. Methodology : This is a cross sectional study that conducted in Department of Pathology, Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan. 70 cases of NPC diagnosed from periods of 2007 to 2017 are included in this study. Out of these 70 cases only 36 cases with its available paraffin embedded tumor were examined for the LMP1 and P16 protein expression. The positivity of LMP1 is based on strong and complete cytoplasm and surface membrane staining in more than 10% of tumor cell. P16 is regarded as positive when there is continuous strong nuclear and cytoplasmic staining pattern in more than 30% of the tumor cells (Block positivity). Prevalence of expression of LMP1 and P16 and clinicopathological data of NPC cases in HUSM is determined and association of the expression of LMP1 and P16 were analyzed using statistical software package SPSS programmed version 24. The strength of associations between variables and LMP1 and P16 is considered statistically significant when p value is same or less than 0.05. Results : From the total of 70 cases of NPC in this study 59 (84.3%) of the cases are male and 11 (15.7%) are female. In 57 cases (81.4%), patients are aged 40 and above and 13 cases aged below 40. Most of the NPC cases are at stage lV (48 cases [68.6%]). Others NPC cases are in stage I, II, and III with percentage of 10.0 %, 14.3 % and 7.1 % respectively. Most of the NPC cases are non keratinizing nasopharyngeal carcinoma (NKNPC), 67 cases (95.7%), 3 cases are keratinizing nasopharyngeal carcinoma (KNPC). Of 36 cases of NPC that proceed with immunohistochemistry staining, 16 (44.4%) cases is LMP1 positive and 20 (55.6%) cases are LMP1 negative. Only 1 (2.8%) out of these 36 cases of NPC is P16 positive. Among 16 cases that are positive for LMP1, 15 of them are male and only 1 case is female (P>0.05). All the positive cases are patients with age group more than 40. 15 cases are Malay and only 1 case is of Chinese ethnicity (P>0.05). All cases that are positive for LMP1 are at the stage lV (P<0.05). 15 out of 34 cases of NKNPC are positive for LMP1. Only1 case of KNPC is positive for LMP1 (P >0.95). Out of our 36 cases of NPC only 1 case is positive for P16 (P>0.95). This 1 case that is positive for P16 is from a male patient, with Malay ethnicity and aged more than 40 years old. The patient is at the stage IV and has NKNPC subtype. Conclusion : This study found high frequency of LMP1 positive in NKNPC cases. Rare case of P16 positive NKNPC also noted. There is an association of LMP1 with the clinical stage at presentation, however no association is noted between the expression of the LMP1 and P16 with the gender, ethnic, age and histology subtype. Due the relatively limited sample size for the immunohistochemistry study, futher work need to carried out using larger sample size.